Histopathology of endoscopic biopsies of gastrointestinal tract lesions with clinical correlation - Gaurav Rastogi; Sanjay Madhukar Chawhan (Acta Medica International, 2023)
Introduction: Because of limited anatomical space and certain unusual clinicopathological features, gastrointestinal tract lesions causes problem in their diagnosis, prognosis, and management. The primary objective of the study is to know the utility of endoscopic biopsy in diagnosing gastrointestinal lesions, and the secondary objective is to correlate the histopathological findings with the clinical symptoms and endoscopic appearance of the lesions. Materials and Methods: The present study is a simple retrospective observational study. Upper and lower gastrointestinal lesions in the form of ulcer, polyp, and growth were biopsied by biopsy forceps using flexible fiberoptic endoscopes. Only adequate biopsies were included in the study. The exact site of the biopsy with clinical data was provided by the endoscopist. Routine histopathological examination was done on the specimens submitted in 10% formalin. The use of special stains was done wherever needed. Results: A total of 100 cases were categorized as nonneoplastic and neoplastic. Friedman and Osborn classification was used for nonneoplastic lesions. The maximum number of cases was seen in 5th–6th decade with male predominance with equal distribution of cases as far as anatomical site is concerned. Conclusion: Targeted biopsies are possible with definitive diagnosis in 90% of cases with safe use of endoscopy. 17% of cases diagnosed on endoscopy were confirmed on histopathology. In 73% of cases, histopathology was essential for further subtyping. Histopathology was mandatory in 8% of the cases. Recommended combined use of endoscopy and histopathology can offer a definitive diagnosis in 98% of cases.